2003
DOI: 10.1029/2002jc001491
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ocean wind and wave data using triple collocation

Abstract: [1] Significant wave height and wind speed fields from ERA-40 are validated against buoy, ERS-1, and Topex altimeter measurements. To do so, we propose and apply a triple collocation statistical model. The model takes into account the random errors in observations and model results and allows the estimation of the variances of the errors. We first examine the case where the random errors of the different systems are independent, but situations where independence is not strictly observed are also considered. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
166
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(172 citation statements)
references
References 21 publications
4
166
2
Order By: Relevance
“…With the improvising of satellite altimeters, the respective blunder for the satellite altimeter has been downsized if compared with the ground-truth buoy, thus the linear-regression method is used for inter-comparison purposes (Durrant et al, 1987). Based on the previous study has concluded the relative error between the satellite altimeter and the ground-truth buoy are relatively equal (Caires and Sterl, 2003). The Ground-truth buoy can be used as a bench-mark for quality control upon the instrument errors and for the affirmation part (Zhoa el al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…With the improvising of satellite altimeters, the respective blunder for the satellite altimeter has been downsized if compared with the ground-truth buoy, thus the linear-regression method is used for inter-comparison purposes (Durrant et al, 1987). Based on the previous study has concluded the relative error between the satellite altimeter and the ground-truth buoy are relatively equal (Caires and Sterl, 2003). The Ground-truth buoy can be used as a bench-mark for quality control upon the instrument errors and for the affirmation part (Zhoa el al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Comparisons of the NCEPR and ERA40 near-surface winds with satellite, buoy, research-vessel and land station winds showed that reanalysis near-surface winds were biased low, particularly in tropical latitudes and for high wind speeds (Swail and Cox, 2000;Smith et al, 2001;Kubota et al, 2002;Caires and Sterl, 2003;Goswami and Sengupta, 2003;Wu and Xie, 2003;Yuan, 2004;Jiang et al, 2005).…”
Section: Ncep-ncar and Ecmwf Reanalysis (Ncepr And Era40) Windsmentioning
confidence: 99%
“…In fact, the appropriate fitting method depends on the relative magnitudes of the measurement errors, or at least their ratio (Cheng and Van Ness, 1999), and orthogonal regression is warranted only if this ratio is near unity, thus treating both variables symmetrically-an approach that appears more justified for the altimeter-altimeter fits of Section 3. Nonetheless, several studies employing triple-collocation analyses (Caires and Sterl, 2003;Abdalla et al, 2011) Jason-2 data RMA yields a slope ÎČ 1 = 1.0519 versus 1.0528 for orthogonal regression, a difference of little consequence and less than the standard error ( Table 2). …”
Section: Buoy-altimeter Statisticsmentioning
confidence: 99%